Gender Dimensions of Migration, Remittances, and Household Economic Security in Nepal - Adhikari, Reena; Adhikari, Gyan Mani; Dhungana, Agya (Voice: A Biannual & Bilingual Journal, 2025)
This paper examines how migration patterns, remittance flows and household economic outcomes are affected by gender in context of Nepal drawing using the data from Nepal Living Standards, Survey IV. The study uses statistical analysis and econometric modeling to examine whether male and female migration create different impacts on welfare of the families in Nepal. The findings suggest that men and women migrate for distinctly different reasons while women primarily for marriage while men migrate seeking employment opportunities. The results further found that female migrants typically earn less as compared to men but send home a larger share of their income than male. Families with female migrants invest higher proportion of their income in education and healthcare while families with male migrants are devoted in the reduction of overall poverty. These findings highlights the distinct contributions of both male and female migrants to household economic security.